Pengaruh AIDA dan Experiental Marketing Terhadap Keputusan Pembelian Produk L-Men di BeFit GYM - cicelia novianti; Ni Putu Widhia Rahayu (Penerbit Goodwood, 2025)
Purpose: To examine how BeFit Gym members' decisions to buy L-Men items are influenced by AIDA and experiential marketing factors. Research methodology: This study employs a quantitative methodology using questionnaires. The acquired data were examined using multiple linear regression and descriptive analytic techniques with the aid of the IBM SPSS 25 program. The analysis consists of classical assumption tests, reliability and validity tests to ensure the quality of the instrument, and hypothesis tests to establish the relationships between variables. The BeFit Gym members completed a questionnaire. Results: The results showed that AIDA and Experiential Marketing had a positive and significant influence on the purchasing decisions for L-Men products at BeFit Gym. Conclusions: AIDA and Experiential Marketing positively and significantly affect purchasing decisions for L-Men products at BeFit Gym, both partially and simultaneously. The application of the AIDA stages and emotionally engaging consumer experiences effectively encourages purchasing decisions. Limitations: The study was only conducted on BeFit Gym members in Bandar Lampung, and the determination of the sample size used the Lemeshow formula with a 10% error rate. Contribution: The results of this study have strong practical implications for the health supplement industry and gym management. By understanding the factors that influence purchasing decisions, companies can design marketing programs that are more personalized and appealing to the consumers.